Performance-enhancing drugs, sport and corporate governance—Lessons from an Australian football club. (June 2017) - Nichol, Matt; Duffy, Mike
Performance-enhancing or 'supplements' usage in sport presents a challenge for sporting clubs and leagues internationally and is, in large part, a legal and governance issue. The authors argue that the increasing commercialization of sport points to the conclusion that it is better that corporate governance has a significant role to play in modern sporting clubs in avoiding such problems. The recent experience of the Essendon Australian Rules Football Club is examined at some length as are the corporate governance practices of other Australian Football League clubs. The article concludes with recommendations for improvements to corporate governance practice in sporting clubs, including increased use of independent directors and board subcommittees.